The role of socio-historic factors and income inequality in global innovation - Rajeev K. Goel; James W. Saunoris (Economics of Innovation and New Technology, 2023)
In order to better understand why some nations are more innovative than others, this paper considers the influence of socio-historic dimensions of colonialism and income inequality. Using data from 72 nations over the years 1997-2018, we find that ethnic income inequality (along with income inequality) and ethnolinguistic fractionalization of the population reduced the pace of innovation. These findings underscore the role of income distribution and other social factors in facilitating innovation. Furthermore, nations with a colonial past were more innovative, ceteris paribus, whereas nations with long histories (longevity) were no different from others. Finally, we found some support for presidential democracies fostering more innovation.
Keywords: O33; O34; O38; 330; innovation; patents; R&D; colonialism; technological change; genetic distance; fractionalization; income inequality; history; path dependence; presidential democracies